PEMIKIRAN HADIS ‘ABDULLAH AL-HARARI Studi Kajian Ulama’ Hadis Modern-Kontemporer - Ianatussoleh; Masruroh (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
This study examines the hadith thought of Abdullah al-Harari, a scholar from Harar, Ethiopia, who made significant contributions to the study of hadith. The research adopts the library research method, focusing on four main aspects: the biography of Abdullah al-Harari, his educational background, the influence of his thoughts on hadith studies, and his ideas regarding hadith. The findings reveal that Abdullah al-Harari, born in the early 20th century and known as "Al-Habashi" due to his Ethiopian heritage, had a profound educational background in Islamic sciences, particularly in hadith, under the guidance of prominent scholars in the Middle East. Abdullah al-Harari's approach to hadith was shaped by traditional principles, emphasizing the critical importance of sanad (chain of transmission) and matan (content) in assessing the authenticity of hadith. He advocated for a meticulous examination of sanad while maintaining respect for the authority of early Islamic scholars (salaf). Additionally, his contributions to the development of tahrij methods and the critical analysis of matan encouraged Muslims to interpret hadith texts within their appropriate contexts. His legacy is evident in his numerous works, which have become key references in Islamic scholarship, particularly in hadith studies. In conclusion, this study highlights that Abdullah al-Harari's thoughts on hadith not only enriched Islamic literature but also offered a systematic and comprehensive framework for understanding and teaching hadith. These findings are expected to significantly contribute to the development of hadith studies in the modern era